Uji Konsentrasi Ekstrak Kulit Buah Jengkol Terhadap Ulat Grayak Spodoptera litura di Laboratorium - Azlansah Azlansah; Alfian Rusdy; Hasnah Hasnah (Jurnal Ilmiah Mahasiswa Pertanian, 2019)
Abstrak.Ulat grayak (Spodoptera litura F.) merupakan hama yang bersifat polifagus, menyerang banyak jenis tanaman pangan dan hortikultura. Serangan hama ini dapat menurunkan kualitas dan kuantitas hasil mencapai 80%, dan serangan berat menyebabkan puso (gagal panen). Larva memakan daun tanaman yang masih muda hingga meninggalkan tulang daun saja. salah satu pengendalian hama pestisida nabati yang efektif adalah Jengkol yang merupakan tanaman yang berpotensi sebagai pestisida nabati karena mengandung senyawa aktif seperti teroid, alkaloid, flavonoid, saponin, tanin dan glikosida, Senyawa aktif dari kulit buah jengkol ini bisa digunakan sebagai pengendali serangga hama ulat grayak (Spodoptera litura). Hama ini bersifat polifagus dan merupakan hama utama pada tanaman pangan dan hortikultura. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL) non faktorial dengan 6 taraf konsentrasi ekstrak kulit buah jengkol, setiap perlakuan diulang sebanyak 4 kali sehingga jumlah unit percobaan menjadi 24 unit. Hasil pengamatan menunjukkan bahwa aplikasi ekstrak kulit buah jengkol berpengaruh terhadap mortalitas larva, persentase luas daun terserang, persentase pupa yang terbentuk dan persentase imago yang muncul. Hasil penelitian menunjukkan bahwa aplikasi ekstrak kulit buah jengkol efektif untuk mengendalikan hama ulat grayak S. litura  pada daun sawi di Laboratorium. Penggunaan ekstrak kulit buah jengkol dengan dosis 10% mengakibatkan mortalitas larva mencapai 85% pada 5 hari setelah aplikasiCONCENTRATION TEST OF JENGKOL SKIN EXTRACT  AGAINST ARMYWORM Spodoptera litura F.  AT LABORATORYAbstract.Jengkol is one of the potential crops as a plant pesticide because it contains active compounds such as terpenoids, alkaloids, flavonoids, saponins, tannins and glycosides. The active compounds of jengkol skin can be used as a control of armywormpest insect (Spodoptera litura). This pest is polyphagous and is a major pest in crops and horticulture.  This study used a completely randomized design (CRD) non factorial with 6 level of djenkol skin extract concentration, each treatment was repeated four times so that the number of experimental units are 24 units. The purpose of this study was to obtain an effective jengkol skin extract concentration which are effective in controlling pests S. litura. in the laboratory. This research was conducted at the Laboratory of Plant Pests, Plant Protection Department-Faculty of Agriculture, University of Syiah Kuala, Darussalam Banda Aceh. The study lasted from August 2015 until October 2015.The results showed that the application of djenkolskin extract has effect on the mortality of larvae. All treatments containing djenkolskin extract in the observation of 5 HSA highest mortality found in the djenkol skin extract concentration (10%) is 85%, and the lowest concentration (2%), is 45%. The percentage of leaf area affected in the 5 HSA observation can be seen in the control treatment (0%) which was significantly different from all other treatments. The higher the concentration of jengkol skin extracts, the lower the percentage of leaf area attacked by S. litura larvae. The highest percentage of pupae is formed in the control treatment (100%) followed by K1 (55%) and the lowest is in treatment K5 (15%). Percentage of pupae that is formed has to do with the mortality of S. Litura larvae in the 5 HSA observation. The highest percentage of imago  that is found in K0 (control) is 80%, while in K1, K2, K3 and K4 treatments are not significantly different, that is ranged from 2.50 to 10.00% but it is significantly different from the K5, that is 0.00%. The results of the study showed that the application of djenkolskin extract is effective for armyworm S. Litura pest control on mustard leaves in the laboratory. The use of the jengkol skin extract with a concentration of 10% cause the mortality of larvae reached 85% after 5 days application.